1970
DOI: 10.13057/nusbiosci/n070202
|View full text |Cite
|
Sign up to set email alerts
|

Germination and breaking seed dormancy of Alpinia malaccensis

Abstract: Abstract. Rivai RR, Wardani FF, Devi MG. 2015. Germination and breaking seed dormancy of Alpinia malaccensis. Nusantara Bioscience 7: 67-72. Alpinia malaccensis belongs to the ginger family, Zingiberaceae, and is generally propagated by vegetative organs. Seed propagation is needed in order to improve the quality of plants through crossbreeding. The hard testa and small endosperm are the main problems in seed germination. The objectives of this research were to determine the best media for germination and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…According to Rajasekharan et al (2016) and Maulidah et al (2019), who investigated A. galanga in South India and Indonesia, vegetative reproduction with rhizomes occurs more frequently and faster in the distribution of A. malaccensis. Many members of Zingiberaceae have been cultivated, and people usually grow Alpinia and other ginger genera using rhizomes because of the opportunity to propagate plants faster this way than from seeds (Cordeiro and Silva, 2003;Rivai et al, 2015). The clonal propagation of Alpinia results in low genetic variance in the population.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rajasekharan et al (2016) and Maulidah et al (2019), who investigated A. galanga in South India and Indonesia, vegetative reproduction with rhizomes occurs more frequently and faster in the distribution of A. malaccensis. Many members of Zingiberaceae have been cultivated, and people usually grow Alpinia and other ginger genera using rhizomes because of the opportunity to propagate plants faster this way than from seeds (Cordeiro and Silva, 2003;Rivai et al, 2015). The clonal propagation of Alpinia results in low genetic variance in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Seed coat hardness is an important factor that affects germination in seeds [32]. Seed dormancy has been reported in several species of the Zingiberaceae, including Alpinia malaccensis Roscoe [9], Alpinia galanga Willd. [10], korarima [11,12], large cardamom [13], and green cardamom [14].…”
Section: Plantlets Adaptation To Ex Vitro Conditionsmentioning
confidence: 99%
“…Hot water treatments have been reported to enhance germination of hard-coated seeds by elevating water and O 2 permeability of the testa [54]. Rivai et al [9] showed that treatment with hot water at 75 • C for 5 min gave the highest germination rate of Alpinia malaccensis Roscoe seeds. However, in our study, the hot water treatment seemed to have a negative effect on the seed germination and growth of black cardamom seedlings.…”
Section: Plantlets Adaptation To Ex Vitro Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that sand is a suitable me- The high TR ratio indicates that the media used is relatively fertile and that sufficient water is available (Orpa et al 2019). According to (Rivai et al 2015), rice husk charcoal has good aeration and drainage properties but low water holding capacity, while coco peat has both high porosity and water holding capacity. Mixing these two media with soil produces an ideal medium for the growth of I. tinctoria L. seedlings, particularly in an unshaded location (0% shade).…”
mentioning
confidence: 99%